Study on performance of prestressed concrete hollow slab beams reinforced by grouting with ultra-high performance concrete. (December 2021) - Zhang, Shouqi; Du, Shizhao; Ang, Yuan; Lu, Zhenbao
Abstract: To reinforce the inclined web shear crack in the shear span of the prestressed concrete hollow slab beam (PCHSB) on a bridge running for 20 years, a new method of grouting reinforcement was developed. Meanwhile, the grouting material corresponding to this method was developed, so as to improve the shear bearing capacity of prestressed concrete hollow slab. To verify the mechanical performance and reinforcement effect of the strengthened PCHSB, the shear resistance tests were carried out to three pieces of full-scale 20m prestressed concrete hollow slab beam after perfusing reinforcement, whose grouting length was 1.5m, 2.0m, 2.5m respectively. The concrete strain, stiffness, bearing capacity, deflection, crack distribution of beams with different perfusing lengths were tested and compared with those of the beam before reinforcement. The results indicated that the new method of grouting reinforcement with UHPC at the end of the beam could improve the mechanical properties of the beam effectively. The grouting material and the original beam had good cooperative working performance under the test load, which could help to improve the shear bearing capacity effectively, and inhibited the development of oblique cracks. Beyond structural test, temperature of the inner structure was onbseved through a temperature sensor. The evolution of temperature showed the temperature peak UHPC material was reduced significantly. Furthermore, the UHPC material had good filling effect after the reinforced beam was cut apart.